2002
DOI: 10.1002/prot.10180
|View full text |Cite
|
Sign up to set email alerts
|

Mapping pathways of allosteric communication in GroEL by analysis of correlated mutations

Abstract: An interesting example of an allosteric protein is the chaperonin GroEL. It undergoes adenosine 5'-triphosphate-induced conformational changes that are reflected in binding of adenosine 5'-triphosphate with positive cooperativity within rings and negative cooperativity between rings. Herein, correlated mutations in chaperonins are analyzed to unravel routes of allosteric communication in GroEL and in its complex with its co-chaperonin GroES. It is shown that analysis of correlated mutations in the chaperonin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
173
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(183 citation statements)
references
References 36 publications
8
173
0
2
Order By: Relevance
“…Positions that are invariant do not contain sufficient information to assess correlated variations, and positions that display random differences can generate spurious correlations. Therefore, we evaluated 3 algorithms to identify covarying positions (24,29,45). In accord with the results of Fodor and Aldrich (46), we found that the OMES method (29) performed well on this data set.…”
Section: Methodssupporting
confidence: 70%
See 2 more Smart Citations
“…Positions that are invariant do not contain sufficient information to assess correlated variations, and positions that display random differences can generate spurious correlations. Therefore, we evaluated 3 algorithms to identify covarying positions (24,29,45). In accord with the results of Fodor and Aldrich (46), we found that the OMES method (29) performed well on this data set.…”
Section: Methodssupporting
confidence: 70%
“…Therefore, we evaluated 3 algorithms to identify covarying positions (24,29,45). In accord with the results of Fodor and Aldrich (46), we found that the OMES method (29) performed well on this data set. The other methods gave spurious correlations as a result of the relatively high degree of conservation in the HCV sequences or because their clustering methods did not perform well in this context.…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…Many early residue contact prediction methods were derived from statistics and information theory, like OMES [8], MI [9], MIp [10] and SCA [11]. However, these methods ignore the transitive correlation between residues and thus generate many false positive results.…”
Section: Author Summarymentioning
confidence: 99%
“…Such works boosted the discovery of coupled residues, which could previously have been identified only by painstaking in vitro approaches such as thermodynamic double mutant analysis [11]. The next step was to summarize information about correlated positions into pathways [15], motifs [1,20], and structural templates [20] in protein families. Today, projects undertake ambitious large-scale recombination [28] or site-directed and combinatorial mutagenesis studies [23] to identify entire building blocks of proteins important to preserve function.…”
Section: Introductionmentioning
confidence: 99%